(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Currently, 290 million people around the world have myopic eye disease. Only 19 million of them are young people under the age of 18. 40% of people with myopia are blind. Today, eye diseases, including myopia, are considered epidemic. Types of myopia, causes of origin, causes of increase, measures to prevent its exacerbation and advice and a number of solutions to ensure that healthy children do not have myopia are considered as urgent problems.